Analisis Perbandingan Kinerja Keuangan antara Perbankan Konvensional dan Perbankan Syariah yang Listed di Bursa Efek Indonesia (Studi Kasus Bank BRI dan Bank Panin Syariah) - Novi Yanti; Yanti Rozalina (Journal of Economics and Management Scienties, 2022)
The purpose of this research is to know: 1) comparison of financial performance between conventional Bank (BRI) and Bank Syari'ah (Bank Panin Syari'ah) listed in BEI period 2011-2015 seen from financial liquidity ratio (Quick Ratio, LDR), ratio solvability (CAR), and Rentability ratio (ROA, BOPO and NPM). 2) Differences in the financial performance of conventional banks (BRI) and Bank Syari'ah (Panin Bank Syari'ah). The population in this research is Bank Rakyat Indonesia and Bank Panin Syari'ah. The sample is the financial statements of the two banks from 2011-2015. The analysis method used is the analysis of liquidity ratio, solvability and Rentabilitas. Hypothesis test using two different test average (independent sample t- test). The results show that quick ratio, LDR, CAR, ROA, BOPO, and NPM Bank BRI is good, because it has been able to reach predefined standards. For Bank Panin Syari'ah only the ratio of CAR, ROA, BOPO and NPM are said to be good, because it has been able to achieve the standards that have been determined despite decreases and increases. As for the ratio of LDR and Quick ratio in Bank Panin Syariah has not been good because during the period 2011-2015 has not been able to reach the standard set by BI at 81% -110% and 15% -20%. Quick Ratio, CAR, ROA and Net Profit Margin of Bank BRI and Bank Panin Syaria'ah there are significant differences. Meanwhile, if seen from the ratio of LDR, and BOPO there is no significant difference between the financial performance of Bank Rakyat Indonesia and Bank Panin Syariah due to significant value greater than alpha 0.05